Implementation Of Enjoy English Learning For Children In Early Age - Nining Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
This service activity aims to enhance and understand to improve the ability of Widodaren Elementary School teachers, especially in teaching English. This training material includes: Learning English in Elementary School, Learning through Songs and Stories, Learning through Crafting, Learning through Games, Performance Learning. The training was held on February 10 march 20 with 20 participants. The training is carried out using lecture, discussion, assignment and guidance methods. Then the participants are required to perform and make lesson plans from each lesson, then given feedback. The results of the training show that elementary school teachers in Widodaren, still need this kind of training to improve their abilities in teaching English. The training has a high appreciation of effectiveness and efficiency because teachers are required to understand English language teaching for the daily progress. Keywords : enjoy learning English, fun learning, early age.